Cultural and Religious Equity and Disparity in the Group Climate Experience of Moroccan Girls in Dutch Residential Youth Care Settings - Rabia Sevilir; Nienke Peters-Scheffer; Peer van der Helm; Dorien Graas; Robert Didden (MDPI AG, 2024)
Background: The group climate within residential youth care institutions is considered a transactional process, both within a group of youth from various cultural backgrounds and between them and their group workers. The ongoing interaction between the cultural characteristics of these girls may influence the quality of the group climate. This study aimed to provide an in-depth account of the living group climate experiences and perceptions of Dutch girls with a Moroccan cultural background in Dutch residential groups. Method: Interpretative phenomenological analysis was employed to explore the girls' group climate experiences. Result: Three major themes emerged, namely (a) level of involvement of Moroccan girls in their living group, (b) perceptions of Moroccan girls' sense of belonging in a living group, and (c) cultural and religious equality or disparity results in two interaction patterns. The findings revealed that equality or disparity in language, culture, and religion affect Moroccan girls' experiences and perceptions of the living group climate. A crucial finding was that cultural and religious disparity leads to interaction patterns wherein the girls pre-emptively exclude themselves from receiving support from native group workers. Conclusion: Professionals must be aware of the cultural and religious dynamics, including the interplay and impact of cultural and religious equality and disparity, influencing Moroccan girls' group climate experiences.